Ultraviolet Photodetector Using Nanostructured Hexagonal Boron Nitride with Gold Nanoparticles - Dong Chan Kim; Hamin Park (Sensors)
Ultraviolet (UV) photodetectors play a crucial role in various applications, ranging from environmental monitoring to biomedical diagnostics. This paper presents the fabrication and characterization of a high-performance UV photodetector using hexagonal boron nitride (hBN) decorated with gold nanoparticles (AuNPs). The hBN flakes were mechanically exfoliated onto SiO2 substrates, and AuNPs were formed via thermal evaporation, resulting in the creation of a plasmonically active surface that enhanced light absorption and carrier dynamics. Raman spectroscopy, transmission electron microscopy, and electrical measurements were performed to comprehensively analyze the device structure and performance. The photodetector exhibited significantly improved photocurrent and responsivity under UV-B (306 nm) and UV-C (254 nm) illumination, with the responsivity reaching an increase of nearly two orders of magnitude compared to that of the pristine hBN device. These improvements are attributed to the synergistic effects of the wide bandgap of hBN and the localized surface plasmon resonance of the AuNPs. These findings demonstrate the potential of AuNP-decorated hBN for advanced UV photodetection applications and provide a pathway toward more efficient and miniaturized optoelectronic devices.